If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + x + 4x + -4 + 3x + 3 = 180 Reorder the terms: 12 + -4 + 3 + x + 4x + 3x = 180 Combine like terms: 12 + -4 = 8 8 + 3 + x + 4x + 3x = 180 Combine like terms: 8 + 3 = 11 11 + x + 4x + 3x = 180 Combine like terms: x + 4x = 5x 11 + 5x + 3x = 180 Combine like terms: 5x + 3x = 8x 11 + 8x = 180 Solving 11 + 8x = 180 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + 8x = 180 + -11 Combine like terms: 11 + -11 = 0 0 + 8x = 180 + -11 8x = 180 + -11 Combine like terms: 180 + -11 = 169 8x = 169 Divide each side by '8'. x = 21.125 Simplifying x = 21.125
| 4n-9n-n= | | 6x-4=26-4x | | 2sin^2x-5sinx-2=0 | | 3/4m=7.5 | | 19x+20+x+10=90 | | x+x+x+x=44 | | 1e+18= | | x/6=3/9 | | -2(4s-5)-10=-3(5s+5)-5 | | 3n+3=-4 | | 123456789-987654321=0 | | (9-10)x= | | -6x^2+5x+6=7.01466 | | 1x+1-2-(3-x)=6-(1-1) | | (3x^2+3x-8)+(3x^2+6x+17)-(6x^2-17)= | | 17-x=33(x+7) | | 6-2(3x-4)=12 | | (3x^2+3x-8)+(3x^2+6x+17)-(6x^2-17)= | | A=2x+2y | | 3t+4=16 | | (3x^2+3x-8)+(3x^2+6x+17)-(6x^2-17)= | | A=2x+2y | | -6x^2+5x+6=1.41666 | | -3+6x=5x-13 | | 8y-9=2-88yip | | 6/5x-8=3/4x | | 27+2x+5+3x-4=180 | | (3x^2+3x-8)+(3x^2+6x+17)-(6x^2-17)= | | ax^2+5x+6=1.41666 | | 6/5x-8=3/4x | | 6/5x-8=3/4x | | -3+6x=5x-13 |